Genomic relationships between Turnera orientalis and T. occidentalis (Turneraceae) - López, Alicia (2010)
Aiming to differentiate Turnera orientalis (2n = 6x = 30) from T. occidentalis (2n = 6x = 30), traditional and molecular cytogenetic techniques were used. Numerous hybrids were obtained from controlled crosses between T. orientalis and T. occidentalis. An analysis of their pollen viability and the failure to obtain F2 provided evidence of reproductive isolation. The present study reports for the first time the karyotype 22 metacentric + 8 submetacentric for T. occidentalis, and confirms the karyotype of T. orientalis. These species differ in a chromosome pair with secondary constriction and satellite. A FISH analysis showed six rDNA sites located on different chromosome pairs. Although the meiotic chromosome pairing of hybrids suggested a close relationship of the two species, the karyotype and mapped location of rDNA sites were different between the taxa, supporting that T. orientalis and T. occidentalis are distinct species.